Low anti-COVID-19 vaccination coverage and high COVID-19 mortality rates in Brazilian elderly - Kupek, Emil (2021)
Introduction: In 2021, Brazil started a nationwide vaccination against COVID-19 but the emergence of the P.1 variant of SARS-CoV-2, more transmissible and resistant to immunity from the previous infection, rapidly led to a record increase in COVID-19 mortality. Methods: Secondary data on COVID-19 deaths and vaccination coverage were retrieved to examine COVID-19 mortality rate (MR) evolution as anti-COVID-19 vaccination advanced in Brazil in 2021. Poisson regression with adjustment for age and federal states was used to calculate the MR. Results; By mid-April 2021, MR increased 2-3 times compared to the already high level in January for the people of 60 years or older, reaching the highest epidemic level of 5-15 per 100.000 in this age group. Despite a declining time trend followed, by the end of May, the MR level was still about 50% and 80% higher for the 40-79 and 80 years or older. The first dose of anti-COVID-19 coverage reached 80% for the 60-69 years old and exceeded 95% for those of 70 years or older, but the second dose was applied to only 26%, 76%, and 64% of the 60-69, 70-79, and 80 years or older, respectively. The average age-standardized MR over the study time was the highest in northern Brazilian states of Rondônia, Amazonas, Acre, and Roraima (range 6-8.4 per 100.000). Conclusion: Anti-COVID-19 vaccination coverage was below the level necessary to protect Brazilians from rising MR between January and May 2021. Urgent measures are needed to increase the vaccine supply and the adherence to non-pharmacological protective measures.